INOKULASI RHIZOBIUM INDIGENOUS DAN TAKARAN PUPUK UREA TERHADAP NODULASI DAN PERTUMBUHAN KACANG NAGARA PADA MEDIA TANAH GAMBUT - Usman, Usman; Hadie, J; Zulhidiani, R. (Fakultas Pertanian Universitas Palangka Raya, 2015)
Purpose of research is to get the right levels dosage of between inoculation Rhizobium indigenous with urea fertilizer as the best combination of nodulation and growth of Nagara bean in peat medium. Design experiment used was a completely randomized design (CRD) factorial two factors. The first factor was levels dosage treatment of Inocuation Rhizobium indigenous: r0 = 0 g (without inoculation); r1 = 100 g and r2 = 200 g kg-1 of seeds. The second factor is levels dosage of urea fertilizer: u0 = 0 kg ha-1 (without urea fertilizer); u1 = 25 kg ha-1 (25%); u2 = 50 kg ha-1 (50%); u3 = 75 kg ha-1 (75%) and u4 = 100 kg ha-1 (100%). The combination of both treatments was 12, with 3 times replication. The result showed that the interaction between inoculation Rhizobium indigenous and dosage of urea fertilizer, significant and highly significant effect on nodulation and growth of Nagara bean in peat media. Inoculation Rhizobium indigenous 200 g kg-1 of seeds with urea fertilizer 50 kg ha-1 (50%) was the best treatment combination for nodulation and growth of Nagara bean in peat media